Socialization of Cyber Crime Threats Ahead of the 2024 Election for the Online Ojek Community: Sosialisasi Ancaman Kejahatan Siber Menjelang Pemilu 2024 untuk Komunitas Ojek Online - Syahtriatna Djusar; Muhamad Sadar (Universitas Lancang Kuning, 2023)
Ahead of the 2024 General Election, cyber threats are expected to increase along with the increasingly massive use of cyberspace for political purposes. Members of the Online Ojek Community are a group of people who are vulnerable to being targeted and